Dinâmica costeira das praias de Tambaú e Manaíra-PB - Vasconcelos, Gustavo Ferreira de (2010)
The purpose of this study is characterize several aspects that set up the scenery of the beaches Tambaú and Manaíra in the city of João Pessoa/PB, where are emphasized the natural and anthropogenic characters that have influence in coastal dynamics as a subsidy to the planning of the area. The studied beaches have an extension of approximately 3,000 meters and they are in a fully urbanized stretch between the end of the Epitácio Pessoa Avenue and the end of the Flávio Ribeiro Coutinho Avenue. These beaches are a sample of how the Paraiba coast behaves, where are observed some stretches that have erosion problems associated with natural dynamics and chaotic urban increase. The theoretical-philosophical abordage leaned on the methods of social sciences, and on the natural sciences. The methodology used in the study consisted of three stages, related between them, the bibliographic and cartographic research that provided technical/theoretical support very important to the development of the research; the stage in the field provided information and data about the mentioned location; and the laboratorial activities were essential to treat, compile and analyze all data and information collected earlier. In the first chapter of this study, there was a discussion about new trends in geomorphologic theory and a discussion about the dynamic of the coastal scenery. In the second chapter, was made a theoretical survey of the various physical elements that set up the coastal scenery of the area. In the third chapter, it was observed that since the 40s, with the opening of Epitácio Pessoa Avenue, the beaches Tambaú and Manaíra began to be occupied. However, from the 70s, a period that was built the Tambaú Hotel the disorderly urbanization process was intensified and started changing the coastal dynamic of the beaches Tambaú and Manaíra. The collected data in the field, present in the fourth chapter of this study, show a larger dynamic characterized by intense morphological variation in Manaíra beach, during the study, and Tambaú beach presented sedimentation during the analyzed period. According to the parameter of Dean, the studied beaches vary from reflective to intermediate stages (Tambaú) and intermediate (Manaíra). However, variations in the shoreline, evidenced by the overlay of aerial photographs and satellite images, pointed to a retreat of the shoreline facing the continent in Tambaú beach and an advance of coastline to the sector (4) in Manaíra beach.